Between distance and commitment. A reflection on the experience of working with/on the victims of State terrorism in Argentina (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
This text proposes theoretical, methodological, and political reflections about the position of the investigators that inquire into the world of victims. In particular, victims of state terrorism in Argentina. The text analyzes what happens when the aim is to find a point of balance between the distance and the compromise. In that sense, it asks itself how to investigate the world of victims without reproducing what they say about themselves and without falling into a position of extreme detachment
Keywords: Victims, State Terrorism, Distance, Commitment, Knowledge, Familism